Earth's Early Atmosphere and Oceans, and The Origin of Life - Shaw, George H. (SpringerBriefs in Earth Sciences, 2016)
This book provides a comprehensive treatment of the chemical nature of the Earth's early surface environment and how that led to the origin of life,including a detailed discussion of the likely process by which life emerged using as much quantitative information as possible. The emergence of life and the prior surface conditions of the Earth have implications for the evolution of Earth's surface environment over the following 2-2.5 billion years. The last part of the book discusses how these changes took place and the evidence from the geologic record that supports this particular version of early and evolving conditions.